Changes in urban land rent due to the use of land-use planning regulatory instruments, Chapinero district, Bogotá, Colombia (2023)
Urban land rent is one of the main attributes of the housing market that enable public space management. This paper evaluates the effect on urban land rent in the Chapinero district (Bogotá, Colombia) of using Decree 120, 2018. This decree is an instrument that enables the development of collective facilities in any area of the city, even where the currentregulations do not allow it. This involves a change in the usage and, in some areas, an increase in the maximum buildability, thus generating a higher land value and influencing the rent calculation. The determination of the differential rent consisted of a property and regulatoryanalysis and the application of the residual and market comparison methods for determining commercial real estate values and thus determining the changes in land values before and after the regulatory instrument. Consequently, land management based on the development of collective facilities in different areas of the city is an opportunity for owners or developers, both public and private, to implement this type of use, thus improving the conditions of the right to the city of the inhabitants in general through the satisfaction of basic needs complementary to housing and the enjoyment of collective spaces for public use.